Redox Behaviour of Cymantrene Fischer Carbene Complexes in Designing Organometallic Multi‐tags. Issue 17 (18th March 2014) - Bezuidenhout, Daniela I.; van der Westhuizen, Belinda; Swarts, Pieter J.; Chatturgoon, Teshica; Munro, Orde Q.; Fernández, Israel; Swarts, Jannie C.
Abstract A series of Group 7 Fischer carbene complexes, [Cp(CO)2MnI=C(OEt)Ar] (Cp=cyclopentadienyl, Ar=Th=thienyl (1 a), Ar=Fu=furyl (2 a), Ar=Fc=ferrocenyl (3 a)) and biscarbene complexes, [Cp(CO)2MnC(OEt)Ar′(OEt)CMn(CO)2Cp] (Ar′=Th′=2, 5‐thienylene (1 b), Ar′=Fu′=2, 5‐furylene (2 b), Ar′=Fc′=1, 1′‐ferrocendiyl (3 b)) was synthesized and characterized. Chemical oxidation of [Cp(CO)2MnC(OEt)Fc] (3 a) and isolation of the oxidised species [3 a][PF6] possessing a MnII centre proved possible below −30 °C in dichloromethane solution. The ESR spectrum of the transiently stable radical cation, [3 a][PF6], confirmed the presence of a low‐spin MnII centre characterized by a rhombic g tensor (gx=1.975, gy=2.007 and gz=2.130) in frozen dichloromethane at 77 K with 55 Mn hyperfine coupling constants A1, A2 and A3 of 115, 33 and 43 G, respectively. Electrochemical studies demonstrated the influence of the Ar substituent on the oxidation potential. All complexes showed that the redox potentials of carbene double bond reduction and MnI oxidation were dependent on the type of Ar group, but only 3 b showed resolved oxidations for the two MnI centres. Surprisingly, MnI oxidation occurs at lower potentials than ferrocenyl oxidation. Density functional theory (DFT) calculations were carried out to delineate the nature of the species involved in the oxidation and reduction processes and clearly confirm that oxidation of MnI is favoured over that of ferrocene.